LOAD FORECASTING METHOD WITH DKL 3.01 - Qoriatul Fitriyah (Technologic, 2011)
DKL 3.01 methods is using econometric approach combined with data analysis of electricity sales and economic growth which is represented by Product Domestic Regional Brutto (PDRB).